Evidence-based consensus guidelines for the management of catatonia: recommendations from the British Association for Psychopharmacology - Rogers, Jonathan P.; Oldham, Mark A; Fricchione, Gregory; Northoff, Georg; Ellen Wilson, Jo; Mann, Stephan C; Francis, Andrew; Wieck, Angelika; Elizabeth Wachtel, Lee; Lewis, Glyn; Grover, Sandeep; Hirjak, Dusan; et al. (Journal of psychopharmacology, 2023)
The British Association for Psychopharmacology developed an evidence-based consensus guideline on the management of catatonia. A group of international experts from a wide range of disciplines was assembled. Evidence was gathered from existing systematic reviews and the primary literature. Recommendations were made on the basis of this evidence and were graded in terms of their strength. The guideline initially covers the diagnosis, aetiology, clinical features and descriptive epidemiology of catatonia. Clinical assessments, including history, physical examination and investigations are then considered. Treatment with benzodiazepines, electroconvulsive therapy and other pharmacological and neuromodulatory therapies is covered. Special regard is given to periodic catatonia, malignant catatonia, neuroleptic malignant syndrome and antipsychotic-induced catatonia. There is attention to the needs of particular groups, namely children and adolescents, older adults, women in the perinatal period, people with autism spectrum disorder and those with certain medical conditions. Clinical trials were uncommon, and the recommendations in this guideline are mainly informed by small observational studies, case series and case reports, which highlights the need for randomised controlled trials and prospective cohort studies in this area.